Pemanfaatan Tepung Umbi Gembolo sebagai Prebiotik dan Pengaruh Waktu Inkubasi Pada Karakteristik Yoghurt Sinbiotik - Rini, Winda Dwi Setiyo; Aini, Nur; Prihananto, Prihananto (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2026)
Gembolo tuber (Dioscorea bulbifera L.) has potential as a prebiotic ingredient due to its relatively high inulin content (10.96%) and the presence of glucomannan as a major polysaccharide. This study aimed to evaluate the effect of gembolo flour supplementation as a prebiotic in synbiotic yogurt containing Bifidobacterium sp. and Lactobacillus acidophilus on the physicochemical, microbiological, sensory characteristics, and antibacterial activity against Escherichia coli. A completely randomized design with two factors was applied: gembolo flour concentration (1, 2, and 3%) and incubation time (16 and 24 h). The resulting synbiotic yogurt was analyzed for pH, total titratable acidity, total lactic acid bacteria (LAB), antibacterial activity against E. coli, and sensory attributes using a scoring test. The best treatment was further evaluated for proximate composition, viscosity, syneresis, and energy content. The results showed that synbiotic yogurt containing gembolo flour had pH values ranging from 3.53 to 3.81, total titratable acidity of 1.5–1.8%, and total LAB counts of 8.72–9.22 log CFU/mL. Antibacterial activity against E. coli produced inhibition zones ranging from 11.42 to 17.77 mm. Both gembolo flour concentration and incubation time significantly influenced the characteristics of synbiotic yogurt. Based on the multi-attribute Zeleny method, the best treatment was yogurt containing 3% gembolo flour with 24 h incubation. This formulation showed a syneresis value of 8.9%, moisture content of 76.1%, ash content of 1.2%, protein 3.92%, fat 2.8%, carbohydrate 16.1%, and energy value of 103.56 kcal/100 g.